Oltre l’intenzione. Etnografia urbana, lavoro sul campo e progettazione territoriale - Paolo Grassi (Archivio Antropologico Mediterraneo)
The relationship established by ethnography develops a bond between anthropologists and interlocutors capable, under certain circumstances, of producing change. This is often a non-directive transformation, an inherent result of the relationship itself which, through dialogue, allows for a critical examination of the positioning and dynamics of a given social arena. On the basis of five years of fieldwork as a member of an interdisciplinary action-research group, in this article I will try to “ground” such considerations, outlining a figure that is, so to speak, “spurious”, i.e. in close contact with other professions and fields of knowledge. The text as a whole will illustrate a role as an anthropologist capable of bringing into play different skills and acting on several levels, beyond the intentionality of the anthropological gesture.